2006
DOI: 10.1007/s00234-006-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the occipital sinus using contrast-enhanced magnetic resonance venography

Abstract: The frequency and anatomical features of the occipital sinus (OS) were analyzed in this study by contrast-enhanced magnetic resonance venography (MRV) with enhanced fast gradient echo three-dimensional (EFGRE3D) and we discuss the clinical usefulness of this method. The study included 555 patients who underwent contrast-enhanced MRV with EFGRE3D, and maximum intensity projection (MIP), multiplanar reformation (MPR) and multiprojection volume reconstruction (MPVR) images were obtained for the regions of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Moreover, one right-sided or left-sided, or total absence of the occipital sinus has been reported [15]. It may also communicate with other sinuses and veins, including superior sagittal, straight, transverse, or sigmoid sinuses, or the superior jugular bulb [39]. By this wide range of communication, it has been reported that occipital sinus may play a significant role as a collateral course in case of other sinuses disease or occlusion.…”
Section: Dural Venous Sinusesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, one right-sided or left-sided, or total absence of the occipital sinus has been reported [15]. It may also communicate with other sinuses and veins, including superior sagittal, straight, transverse, or sigmoid sinuses, or the superior jugular bulb [39]. By this wide range of communication, it has been reported that occipital sinus may play a significant role as a collateral course in case of other sinuses disease or occlusion.…”
Section: Dural Venous Sinusesmentioning
confidence: 96%
“…It starts at the foramen magnum, where it communicates with the vertebral venous plexus and/or the marginal sinus, and ends cranially mainly at the confluence of sinuses [39]. Variation in the anatomy of the occipital sinus has been recognized.…”
Section: Dural Venous Sinusesmentioning
confidence: 98%
“…Blood flow through enlarged dural veins in superior sagittal sinus occlusion has been demonstrated, and may represent one collateral path. 24 Two additional paths include the vein of Labbe 25 (a cortical vein that drains the lateral surface of the hemispheres) and the occipital sinus 26 (draining directly from the torcular). Both of these structures can, albeit with variation, drain into the sigmoid sinus, bypassing the distal TS where the majority of stenoses in patients with IIH occur.…”
mentioning
confidence: 99%
“…This nding was evidenced by Bono et al [22]. This lack of association may be due to the compensatory effect of vein of Labbe and occipital sinus [23,24].…”
Section: Discussionmentioning
confidence: 75%